Manajemen Agribisnis Komoditas Anggrek (Orchidaceae) Di PT Anugerah Anggrek Nusantara Kabupaten Kediri - Rachmawati, Devi; Yulanda, Kiki Asri; Wulandari, Diny; Ria, Vina Yunita; Novrianto, Jonathan Andreco (Universitas Islam Kadiri, 2024)
This research to determine the agribusiness management of orchid commodities at PT Anugerah Anggrek Nusantara. PT Anugerah Anggrek Nusantara is located in Sumberpetung, Sempu Village, Ngancar District, Kediri Regency, East Java. The research used is descriptive analysis. The data sources used in this research are primary data through observation, interviews, and documentation while secondary data is through literature studies. The results of the research show that agribusiness management at PT Anugerah Anggrek Nusantara is carried out with several activities including, procurement of raw material inputs, production processes, and marketing. Procurement of production inputs depends on the activities of the production stages obtained from offline and online stores. Production activities at PT Anugerah Anggrek Nusantara consist of pollination, tissue culture, acclimatization, repotting, maintenance, harvesting and marketing. Marketing activities in this company apply the marketing strategy of the 7P marketing mix, namely product, price, promotion, place, people, process and physical advice.